Studi Perencanaan Fasilitas Integrasi Moda Pada Terminal Baranangsiang Kota Bogor - Amalia Fajar, Risma; Murtedjo, Tedy; Rulhendri (Journal of Applied Civil Engineering and Infrastructure Technology, 2024)
Transportation mode shift is a node that connects various public transportation into a network. If switching between these modes of transportation can be designed to be easier, faster, and more convenient, then the integration and flexibility of the network as a whole will increase. This study aims to evaluate, analyze and then plan the needs of modal integration facilities based on SPM. identify the condition of existing modal integration facilities at the current terminal, analyze the level of willingness, satisfaction and interest according to the perceptions of transport passengers towards the existing modal integration facilities at Baranangsiang Terminal, and obtain values from respondents on modal integration facilities that are needed or have not been fulfilled at Baranangsiang Terminal Bogor city. This study uses a descriptive method with a quantitative approach. The results of this study are that the Bogor City Baranangsiang Terminal from January to June 2023 has reached 13,490 passengers, which on average reaches 2,248 people per day. Based on the aspect of satisfaction seen from the willingness of respondents to fill out the questionnaire, it was found that the lowest level of satisfaction was pedestrian facilities, lighting, trash cans, the presence of bicycle lanes, disability lanes and signs in the terminal. This aspect of interest is considered very important for terminal users.